The Multiple ‘Means’ of Drawing for Design. Tests in Repurposing Industrial Products (diségno, 2022)
Drawing plays a specific role in forming a code of thought, which is built through progressive layering and unfolds above all in writing, whatever the instrument used. In this sense, its multiple prerogatives articulate that indispensable yet necessary language, not only to communicate a design project but also to implement that fundamental procedure of controlling the design process. From an operational point of view, this translates into the practice of using different of drawing to tell about the project.With this in mind, this article presents some experiences in research and teaching conducted in an  experimental/laboratory form on the subject of repurposing certain existing industrial products by studying their ability to accept modifications on different levels. This creative process for a renewed concept/functionality of products was conducted through two closely related phases. The first is cognitive and aimed at activating processes of true appropriation/reconstruction of the design process through graphical operations to ‘recognize’ the object. The second is to study appropriate transformations aimed at re-presenting the modified product according to different planes of communication or different problematic levels of in-depth examination.
Keywords: product design; drawing; transformation; cognitive models; interpretational/descriptive methods